Maritale Rape dalam Perspektif Qira’ah Mubādalah dan Undang-Undang Tindak Pidana Kekerasan Seksual - Muhammad Rosyid Ridho; Silvia Nahla Sari (Intitut Agama Islam Riyadlotul Mujahidin Ngabar (IAIRM) Ponorogo, 2023)
The marriage bond gives legal consequences to the emergence of the same rights and obligations as humans. One of the human rights violations against women in husband and wife relationships is marital rape or rape within marriage. Through the Qira'ah Mubādalah method of reading verses that regulate intimate relations between husband and wife, Kiai Faqih explains that the desire for sexual relations between husband and wife must come from both of them or, even if there is coercion and violence, this is very contrary to Mubādalah principles. Marital rape itself has a record of 57 cases in the National Women's Commission's CATAHU in 2020. With the fact that there are marital rape cases, it is necessary to have a legal umbrella to prevent and regulate the resolution of the consequences arising from the sexual crime of marital rape, especially against victims, because it is in the Criminal Code itself. Regarding marital rape, there is no regulation, so the Law on Criminal Sexual Violence which has been passed is the legal umbrella for sexual crimes in marriage, namely marital rape which is regulated in Article 6 of the Law on Non-Criminal Sexual Violence. In this paper, the author formulates the problem of this research as: 1) What are the forms of coercion between husband and wife in marriage? 2) How is the sexual relationship between husband and wife in the Qira'ah Mubādalah perspective? 3) How does marital rape correlate from Qira'ah Mubādalah's perspective with Article 6 of the Sexual Violence Crime Law? This research includes a qualitative research model with the type of library research.